Analysis of Criteria for School Exam Questions in Science Subjects at SMP Negeri 2 Ngoro - Sulistyowati, Sulistyowati (Department of Biology Education, Faculty of Teacher Training and Education, Universitas Wijaya Kusuma Surabaya, 2025)
Quality test questions are questions that can provide precise information about student learning outcomes. The purpose of this study was to analyze the quality of the Science Subject School Exam questions at SMPN 2 Ngoro for the 2022/2023 academic year which consisted of 20 questions. The research sample consisted of 62 student responses in class IXA and IXF with purposive sampling method. This study uses a quantitative and qualitative approach with data analysis techniques using the SPSS version 25 application and Microsoft excel. The results showed that the items used were classified as difficult 15%, items classified as moderate 60% and items classified as easy 25%. The analysis of the discriminatory power of the questions showed that 70% of the items already had good discriminating power and the other 30% did not have good discriminating power and needed to be revised. The analysis of the distractor options from the items found that 96% of the total distracting options on these items were good and the rest were not good and needed to be revised.